Angstrom-scale replication of surfaces with crystallized bulk metallic glasses. (December 2021) - Chen, Z.; Xie, Y.; Datye, A.; Thornton, J.; Schroers, J.; Cha, J.J.; Schwarz, U.D.
Abstract: The replication of single-crystalline strontium titanate (STO) surfaces through thermoplastic forming with a Pt57.5 Cu14.7 Ni5.3 P22.5 alloy that is in a glassy state during forming but subsequently heated in situ until crystallized is investigated. In contrast to postforming ex situ heating to crystallization, which roughens the surface, atomic force microscopy measurement of replicas that crystallize while still being in contact with the mold reveals an exact angstrom-scale replication of the terraced surface features found on the STO molds. The structure and degree of crystallinity of the metallic replicas is characterized by x-ray diffraction, differential scanning calorimetry, and high-resolution transmission electron microscopy. Thereby, it is found that even though the bulk of the sample fully crystallizes, a thin surface layer remains partly amorphous despite extended heating above typical bulk crystallization temperatures and times. The existence of this layer is not only key to overcome the intrinsic limits of replication accuracy that would be imposed by the lattice parameters if the alloy were to fully crystallize but also expected to improve many of the part's mechanical and chemical properties while the crystalline bulk provides stability at elevated temperatures.